The effects of the reinforcement on the degradation behavior of cloth-type CFRP under microwave dielectric heating - Nguyen, Phuong Ngoc Diem (Animo Repository, 2009)
Carbon fiber reinforced plastic (CFRP) composites are being used increasingly in many industrial applications. In general, the properties of fiber reinforced composites depend strongly on both fiber and matrix characteristics. Nowadays, CFRP is considered as a difficult material for degradation processes due to its high strength and thermal resistance. Based on this property, how to treat CFRP wastes efficiently has became a very important problem. However, with reinforced carbon fiber - a good microwave absorber, CFRP can be degraded easily under microwave irradiation. This is the reason why in this paper, the effects of microwave irradiation on two kinds of Cloth-type CFRPs were being examined. The results of this study can be summarized as follows: (1) The percentage weight loss of 195°C Tg, 10 layers, and 3k filaments Cloth-type CFRP samples reached to 17% after 54 seconds at 400W; and 11% weight loss for 115°C, 3 layers, and 12k filaments Cloth-type CFRP samples after 900 seconds at 400W; (2) Under 350W and 400W microwave irradiation, the temperature of 195°C Tg, 10 layers, and 3k filaments Cloth-type CFRP increase faster and reached higher value as comparing to 115°C, 3 layers, and 12k filaments samples; (3) The bending strength and elastic modulus values of Cloth-type CFRP plastic decrease with increasing residence time; (4) Microwave effect on the bonding between matrix and carbon fiber and made the composites' strength and elastic modulus reduced.